Pengaruh Praktik Environmental, Social, and Governance terhadap Nilai Perusahaan dengan Pengungkapan Emisi Karbon sebagai Variabel Mediasi - Agni, Muhammad Tektona; Anis, Idrianita (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study discusses company value in the property and real estate industry, which can be influenced by various factors. The author explores the relationship between ESG Practice variables and the mediation of Carbon Emission Disclosure on Company Value. The aim of this research was to obtain the latest knowledge according to issues currently occurring in society. The analytical method used by researchers is multiple linear regression using purposive sampling techniques. In this research, the author uses secondary data in the form of annual and sustainability reports of major companies in the property and real estate industry for 2015-2022 which are listed on the Indonesia Stock Exchange. From the results of the research conducted, it was concluded that the variable ESG Practices had a positive effect on Company Value, ESG Practices had a positive effect on Carbon Emission Disclosure and ESG Practices mediated by Carbon Emission Disclosure had a positive effect on Company Value.